Carnitine Palmitoyltransferase II Deficiency (CPT II) Followed By Rhabdomyolysis and Acute Kidney Injury - Gjorgjievski, Nikola; Dzekova Vidimliski, Pavlina; Petronijevic, Zvezdana; Selim, Gjulshen; Dejanov, Petar; Tozija, Liljana; Shikole, Aleksandar (Scientific Foundation SPIROSKI, 2018)
Carnitine palmitoyltransferase II deficiency (CPT II) is an autosomal recessive disorder and the most common inherited disorder of mitochondrial long-chain fatty acid oxidation, characterised by attacks of myalgia and myoglobinuria. The most common "classic" myopathic form occurs in young adults and is characterised by recurrent episodes of rhabdomyolysis triggered by prolonged exercise, fasting or febrile illness.